Urban Flood Depth Estimate with a New Calibrated Curve Number Runoff Prediction Model - Ling L.; Yusop Z.; Chow M.F. (Institute of Electrical and Electronics Engineers Inc., 2023)
Floods; Forecasting; Infiltration; Rain; Sewage; Soil conservation; Statistical methods; Storms; Bootstrap; Curve numbers; Drainage infrastructure; Inferential statistics; Rainfall-runoff modeling; Runoff prediction model; Soil conservation services; Sum of squared errors; Runoff